As letras como unidades históricas na construção do discurso - Arena, Dagoberto Buim [UNESP] (FapUNIFESP (SciELO), 2013)
This paper proposes we grant graphemes - the constituents of words in situations of discursive constructions - the status of meaning carrying units, in much the same way Vigotski granted the phoneme such status in relation to the spoken word. This paper also seeks to analyze these units in singular manifestations in acts of appropriation of the written language, based on data created by a six-year-old child in a discursive situation. To perform this task, we also referred to Bakhtinian studies on the role of the other in our relation with language. Since the analysis indicated spelling approximations to records found in old Portuguese, historical grammar research of Portuguese was also used. The findings indicate the diversity of reference sources for letter selection by the child, according to its function in the composition of the word.
Letters as historical units in the construction of speech
Keywords: Discourse; Functions of letters; Literacy; Orality and literacy; Spelling of portuguese